Bayesian modeling predicts age and sex are not required for accurate stature estimation from femoral length. (August 2018) - Reynolds, Mikaela S.; MacGregor, Donna M.; Alston-Knox, Clair L.; Meredith, Matthew; Barry, Mark D.; Schmutz, Beat; Gregory, Laura S.
Abstract: Despite the recognized flaws in applying traditional stature estimation equations such as those of Trotter and Gleser (1952) [5] to a contemporary population, there are currently no available alternatives for stature estimation in Australia that address these limitations. Post mortem computed tomography (PMCT) DICOM scans of the left and right femora were acquired from 76 Australian deceased individuals aged 17–76 years for metric analysis. Femoral bicondylar length, femoral epicondylar breadth and anterior–posterior (AP) diameter, medial-lateral (ML) diameter, circumference and cortical area at the femoral midshaft were measured on three-dimensional (3D) models to build statistical models for estimating stature. In addition, Australian individuals aged 16–63 years (n = 111) were measured in standing and supine positions to aid in the adjustment of supine stature of deceased individuals utilized in this study to standing stature. The results of this preliminary evaluation strongly indicate that the optimal model for estimating stature includes bicondylar femoral length and epicondylar breadth, that the effect of sex as an independent variable is very low, and there is limited practical benefit in including age in the estimation of stature. Our study indicates that the Australian population sampled represents a small yet significant shift in stature from the original Trotter and Gleser sample. Additionally, in the case of fragmentary remains, it was found that epicondylar breadth and AP diameter had the highest probability of accurate stature estimation in the absence of bicondylar femoral length. As stature forms a significant component of a biological profile and therefore aids in the personal identification of human remains, it is important that forensic anthropologists utilize the most accurate methodologies available. Stature estimation of Australian individuals is therefore achieved with higher accuracy through utilizing the femoral equations proposed in this study.